PHYTOCHEMICALS & ANTIOXIDANT ACTIVITY OF ANDALIMAN SEEDS AND FLESH - Salim, Reny (Prodi Kimia, 2024)
Andaliman fruit is one kind of spice that has antioxidant benefits. Secondary antioxidants are needed by the human body to combat internal and external free radicals. Effort can be made to eliminate these free radicals by eating foods that have active compounds with adequate antioxidant activity. The study aims to identify the group of secondary metabolite compounds and the antioxidant activity of fruit flesh and seeds. The extraction method used is maceration using a 70% ethanol-acidified solvent. The phytochemical screening method is a color reaction. The method of antioxidant activity is DPPH. Result of the phytochemical screening of simplisia and extract of fruit (seeds and flesh) show the presence of alkaloids, flavonoids, terpenoids, and tannins. The results of the phytochemical screening of seed simplisia revealed the presence of alkaloids, terpenoids, and tannins. The antioxidant activity of seed and flesh extracts falls into the strong category with IC50 values of (56,80 and 52,32) ppm. It has been suggested that the maceration method using the acidified solvent affects the antioxidant activity of seeds and flesh of the andaliman fruit.